A Human Telomerase-associated Nuclease - Oulton, Rena (The American Society for Cell Biology, 2004)
Ciliate and yeast telomerase possess a nucleolytic activity capable of removing DNA from the 3′ end of a single-stranded oligonucleotide substrate. The nuclease activity is thought to assist in enzyme proofreading and/or processivity. Herein, we report a previously uncharacterized human telomerase-associated nuclease activity that shares several properties with ciliate and yeast telomerases. Partially purified human telomerase, either from cell extracts or recombinantly produced, demonstrated an ability to remove 3′ nontelomeric nucleotides from a substrate containing 5′ telomeric DNA, followed by extension of the newly exposed telomeric sequence. This cleavage/extension activity was apparent at more than one position within the telomeric DNA and was influenced by sequences 5′ to the telomeric/nontelomeric boundary and by substitution with a methylphosphonate moiety at the telomeric/nontelomeric DNA boundary. Our data suggest that human telomerase is associated with an evolutionarily conserved nucleolytic activity and support a model in which telomerase-substrate interactions can occur distal from the 3′ primer end.